An Overview of Rosacea (Canadian Dermatology Today, 2022)
Rosacea is a well-described chronic cutaneous syndrome with a constellation of different clinical signs and symptoms, with key components including persistent facial erythema and inflammatory papules and pustules primarily affecting the central face, and often with repeated remissions and exacerbations. Characteristic additional features are facial telangiectasias, frequent facial flushing, facial erythema and edema that is non-pitting and ocular and phymatous changes.